1992
DOI: 10.1007/bf03159973
|View full text |Cite
|
Sign up to set email alerts
|

Polyamine metabolism in different pathological states of the brain

Abstract: Biosynthesis of the polyamines spermidine and spermine and their precursor putrescine is controlled by the activity of the two key enzymes ornithine decarboxylase (ODC) and S-adenosylmethionine decarboxylase (SAMDC). In the adult brain, polyamine synthesis is activated by a variety of physiological and pathological stimuli, resulting most prominently in an increase in ODC activity and putrescine levels. The sharp rise in putrescine levels observed following severe cellular stress is most probably the result of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
66
0

Year Published

1995
1995
2005
2005

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 93 publications
(67 citation statements)
references
References 119 publications
(154 reference statements)
1
66
0
Order By: Relevance
“…*p Ïœ 0.05, **p Ïœ 0.01 compared with sham (n Ï­ 6); # p Ïœ 0.01, MDL 72527-treated ischemic (n Ï­ 5) compared with untreated ischemic with 1-day R and not significant compared with sham; ## p Ïœ 0.01, MDL 72527-treated ischemic (n Ï­ 5) compared with untreated ischemic with 1-day R and p Ïœ 0.05 compared with sham. putrescine (Dempsey et al, 1991;Paschen, 1992a;Kindy et al, 1994;Rao et al, 1995Rao et al, , 1998Henley et al, 1996;BaƟkaya et al, 1996a,b). These changes correlate with the degree of injury and with neuronal death (Kindy et al, 1994;Henley et al, 1996;Ivanova et al, 1998).…”
Section: Ssat/pao May Largely Determine Putrescine Levels 1 Day Aftermentioning
confidence: 99%
See 1 more Smart Citation
“…*p Ïœ 0.05, **p Ïœ 0.01 compared with sham (n Ï­ 6); # p Ïœ 0.01, MDL 72527-treated ischemic (n Ï­ 5) compared with untreated ischemic with 1-day R and not significant compared with sham; ## p Ïœ 0.01, MDL 72527-treated ischemic (n Ï­ 5) compared with untreated ischemic with 1-day R and p Ïœ 0.05 compared with sham. putrescine (Dempsey et al, 1991;Paschen, 1992a;Kindy et al, 1994;Rao et al, 1995Rao et al, , 1998Henley et al, 1996;BaƟkaya et al, 1996a,b). These changes correlate with the degree of injury and with neuronal death (Kindy et al, 1994;Henley et al, 1996;Ivanova et al, 1998).…”
Section: Ssat/pao May Largely Determine Putrescine Levels 1 Day Aftermentioning
confidence: 99%
“…Several mechanisms of polyamine-dependent neuronal injury have been proposed: (a) overactivation of calcium fluxes and neurotransmitter release in areas with an overproduction of putrescine (Koenig et al, 1983); (b) overstimulation of the NMDA receptor complex caused by a release of polyamines into the extracellular space during or after CNS trauma; or (c) production of hydrogen peroxide and 3-acetamidopropanal through activation of the interconversion of spermine and spermidine into putrescine via SSAT/PAO (Morgan, 1987(Morgan, , 1998Paschen, 1992a;Seiler, 1995). SSAT is the rate-limiting step in the catabolism of polyamines (Casero and Pegg, 1993;Suppola et al, 1999), and the activation of SSAT after transient ischemia has been indicated by increased levels of SSAT mRNA (Zoli et al, 1996).…”
mentioning
confidence: 99%
“…[113][114][115] Polyamines have a number of functions in the brain, [116][117][118][119] and it is known that these endogenous compounds play an important role in excitotoxicity. 120,121 Because BBB functionality is also influenced by polyamines, a relationship among neurodegeneration, polyamines, and BBB function [122][123][124] is indicated.…”
Section: E537mentioning
confidence: 99%
“…A prolonged activation of the NMDA receptor is associated with neuronal damage and a functional receptor is needed for spatial learning [65]. Taken together the results obtained with transgenic animals with greatly elevated brain putrescine, such as protection from seizure activity and ischemiareperfusion damage as well as impaired spatial learning, led us conclude that the strikingly expanded brain putrescine pools and the up to 40-fold increased molar ratio of putrescine to the higher polyamines in the transgenic animals create a partial blockade of the NMDA receptor [1].…”
Section: Central Nervous Systemmentioning
confidence: 99%